Optimization of FISIP's Website and Social Media in Efforts to Internationalize and Improve Public Information Services - Pramono, Didi; Husna, Vina Nurul; Mumpuni, Restu Ayu; Wijayanti, Tutik; Hanafi, Asti; Refiyan, Tio Putra; Kyarto, Abdullah Fariz; Asih, Rizqi Amalia Dwi (Forum Ilmu Sosial, 2024)
The objectives of the study are: 1) optimizing the website of FISIP as an effort to internationalize and provide public information; 2) optimizing the social media of FISIP as an effort to internationalize and provide public information. This research was carried out using a collaborative action research approach. The research steps include problem identification, action planning, partner collaboration, implementation, observation and monitoring, reflection and evaluation, and corrective actions. The study results show that the FISIP Public Relations and Reputation Team has collaborated with the University Public Relations Team, UNNES TV, and external mass media. Tangible actions that have been implemented include website content evaluation workshops, preparation of international study program profiles, workshops on strategies for increasing international publications through websites, development of study program promotion content, both posters and videos, optimization of the promotion of new Communication Science study programs, development of public complaint services through the UNNES PPID, Helpdesk, and Report features on the FISIP website. Continuous improvement is essential to ensure that all work programs implemented by the FISIP Public Relations Team can run smoothly and achieve the goals set.